Detection of infrared light through stimulated four-wave mixing process - Zhang, Wei-Hang; Peng, Jing-Yuan; Li, En-Ze; Ye, Ying-Hao; Zeng, Lei; Dong, Ming-Xin; Ding, Dong-Sheng; Shi, Bao-Sen (Frontiers in Quantum Science and Technology, 2022)
Infrared optical measurement has a wide range of applications in industry and science, but infrared light detectors suffer from high costs and inferior performance than visible light detectors. Four-wave mixing (FWM) process allows detection in the infrared range by detecting correlated visible light. We experimentally investigate the stimulated FWM process in a hot $^{85}$Rb atomic vapor cell, in which a weak infrared signal laser at $1530~$nm induces the FWM process and is amplified and converted into a strong FWM light at $780~$nm, the latter can be detected more easily. We find the optimized single- and two-photon detunings by studying the dependence of the frequency of input laser on the generated FWM light. What's more, the power gain increases rapidly as the signal intensity decreases, which is consistent with our theoretical analysis. As a result, the power gain can reach up to 500 at a signal laser power of $0.1~μ$W and the number of detected photons increased by a factor of 250. Finally, we experimentally prove that our amplification process can work in a broad band in the frequency domain by exploring the response rate of our stimulated FWM process.